Cyanobacterium Nostoc species mitigate soybean cyst nematode infection on soybean by shaping rhizosphere microbiota - Yin, Chuntao; Lahr, Nathan; Zhou, Ruanbao (Frontiers in Microbiology, 2025)
Soybean cyst nematode (SCN, Heterodera glycines Ichinohe) is the most devastating and yield-limiting pathogen that threatens soybean production globally. Sustainable SCN disease management strategies are needed. In this study, a cyanobacterial strain was isolated from SCN-infected soybean soil and identified as Nostoc punctiforme using the cyanobacterial 16S rRNA gene sequence. When susceptible soybean plants were grown in the SCN-inoculated soil, N. punctiforme inoculants significantly reduced the total number of SCN eggs and second-stage juveniles (J2s), compared to the control with SCN inoculation only. Further microbial analysis showed that N. punctiforme inoculants changed the bacterial and fungal communities in the soybean rhizospheres and significantly increased the relative abundance of several bacterial and fungal species with potential nematicidal activities, suggesting the changes of soybean rhizosphere microbiota may partially contribute to the activity of N. punctiforme inoculants against SCN. However, N. punctiforme inoculants did not directly induce soybean defense reactions against SCN. Thus, N. punctiforme may be a potential microbial source against SCN invasion in soybean.